(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
INTRODUCTION Lung cancer is the world’s most diagnosed cancer and kills around 1-2 million people per year. It is the fourth most frequently diagnosed cancer among females globally and the second most prevalent cause of mortality from cancer. Palliative thoracic radiation is an useful way to treat the symptoms. This palliative radiotherapy is also used to treat svc syndrome in carcinoma lung. The palliative radiotherapy schedule varies considerably in different centres. The purpose of above mentioned topic is to compare two palliative dose fraction (10 FRACTIONS OF 3GRAY VS 5FRACTIONS OF 4GRAY) in view of symptom relief, disease control, toxic effect.MATERIALS AND METHODS A total of 50 patients of locally advanced or metastatic carcinoma of lung taken for the study. All patients are histological proven cases of carcinoma lung. All (50) patients in study were divided in two equal arms- arm A arm B. This arm A patients received 3Gyfraction, 10 fractions from EBRT co60 over 2 weeks, and the arm B patients received 4Gyfraction 5fractions from EBRT co60 over 1 week.All the patients were treated in supine position and assessed for symptom relief on 1st day 4th day followed by last day of treatment 1st month 2nd month and 3rd month of starting of treatment. Also assessed for toxicity like skin reaction, pneumonitis, esophagitis.The treatment stopped when the patient developed grade 4 skin reactions or pneumonitis or esophagitis. At the end of 1month post radiotherapy X ray chest were taken and compared the size of the mass with X ray taken before radiotherapy, based on that disease response to palliative radiotherapy were assessed and compared.RESULTS This Study population had median age at presentation of 65 years with a range of 30-89 years, median age of 65yrs for males and 55 years for females in both arms. Majority of patients were in 6th decade of life (48) at presentation 24 of the patients were having age less than 50 years. In the population studied male female sex ratio was 11.51. In present study population, most of the patients were having multiple symptoms at presentation. Dyspnea (92 in arm A arm B), Cough (92 in arm B 88 in arm B) Chest pain (80 in arm A, 72 in arm B) hemoptysis (40 in arm A 44 in arm B) were most common presentation. On completion of treatment 52 patients in arm 16 patients in arm B got symptom control for dyspnea, 28 patients in arm A 24 patients in arm B got symptom control for cough, 52 patients in arm A 20 patients in arm B got symptom control for chest pain, 16 patients in arm A 8 patients in arm B got symptom control for hemoptysis. In this study toxicities like oesophagitis, pneumonitis, skin reaction were noticed. Skin reactions were more commonly noticed (28 in arm A 52 in arm B) among toxicities, after that pneumonitis (24 in arm A 40 in arm B) and esophagitis (8 in arm A 20 in arm B). Toxicities are more with arm B than arm A. There is no grade III and grade IV toxicities noticed in this study. There was no complete response of disease to radiation in both arms. Partial response noticed in 36 of patients in arm A 20 of patients in arm B at the end of treatment (p value >0.05, non significant), progression of disease observed in both arms and it was noticed that disease progression is more seen in arm B than arm A.CONCLUSION The above study was performed for 50 patients and reached a conclusion that, 3Gyfraction, 10 fractions regime provided better results in symptom relief and disease control with minimal radiation induced toxicity when compared to 4Gyfraction, 5 fractions. This study shows non inferiority of 4Gyfraction, 5 fractions as compared to the established 3 Gy fraction, 10 fractions regime, with good symptom response and acceptable toxicity.